Cooling efficiency in furnace design (2013)
During melting, reduction or thermal treatment of a steel charge, the input of energy (either chemical or electrical) is indispensable to guarantee the viability of the process. Under these circumstances, it will be reasonable to design the furnace lining in such a way that heat loss through the walls is minimized. Nevertheless, it can be proved that, for some situations, it is more efficient to withdraw as much heat as possible from the walls than trying to thermally isolate the system. The work presents recommendations for the design of walls and cooling systems in furnaces obtained by quantitative analysis of temperatures reached in specific locations of the furnace using the nodal wear model. The analysis indicates that the wear process of the lining may be controlled if all the elements that intervene in the process are known.